Atendimento no Banco Central: uma pesquisa sobre a satisfação dos clientes - Prata, Claudia Marquesi (1999)
Customer satisfaction is a well-known area in the private sector. This research intends to introduce it in a public organization - the Central Bank of Brazil. The purpose of the study is to assess the degree of customers satisfaction with the service provided by the Service Centers of that institution. First, it discusses the relationship between the service to citizens in government agencies and the refinement of the concept of citizenship. Then, it builds the field research on the scientific basis of the literature of customer satisfaction and service quality. It describes the disconfirmation paradigm and analyses the affective basis of satisfaction, as well as theories such as Assimilation, Contrast, Assimilation-Contrast, Equity and Attribution. The peculiarities of services and service quality are also discussed. Based on the reviewed theory, it develops a questionnaire that was tested and refined before it was used in structured interviews with the public of the Service Center of Central Bank's Regional Office in Rio de Janeiro. The results suggest a high levei of satisfaction and the study concludes with practical implications and directions for further research.